2020
DOI: 10.9778/cmajo.20200010
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric drug data in Canadian drug monographs: a descriptive analysis

Abstract: ptimizing pharmacotherapy in children has been the goal of many American and European legislative initiatives. These initiatives have been introduced to mandate or incentivize pharmaceutical companies to conduct pediatric drug studies and provide equally rigorous therapeutic information for children as for adults. 1-3 In the United States, the Best Pharmaceuticals for Children Act (BPCA; 2002) and the Pediatric Research Equity Act (PREA; 2003) are some of the acts that encourage pediatric drug development. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…While these important legislative achievements aimed to protect citizens from unproven and unsafe pharmaceuticals through research and regulatory oversight, they had the unintended consequence of excluding children, both formally and informally, from both the research and regulatory enterprise. In the subsequent half-century, as research and regulatory systems evolved to optimize the safety and efficacy of marketed therapies for adults, high-quality data informing the safe and effective use of medications in infants, children and youth were rarely generated (Bourgeois et al 2012) and were even more rarely submitted to regulators for review (Carmack et al 2020;Raja et al 2020). This dearth of data led Harry Shirkey in the late 1960s to label children as "therapeutic orphans" (Shirkey 1968: 119).…”
Section: Introductionmentioning
confidence: 99%
“…While these important legislative achievements aimed to protect citizens from unproven and unsafe pharmaceuticals through research and regulatory oversight, they had the unintended consequence of excluding children, both formally and informally, from both the research and regulatory enterprise. In the subsequent half-century, as research and regulatory systems evolved to optimize the safety and efficacy of marketed therapies for adults, high-quality data informing the safe and effective use of medications in infants, children and youth were rarely generated (Bourgeois et al 2012) and were even more rarely submitted to regulators for review (Carmack et al 2020;Raja et al 2020). This dearth of data led Harry Shirkey in the late 1960s to label children as "therapeutic orphans" (Shirkey 1968: 119).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A recent study showed that only 47% and 28% of product monographs of newly approved medications in Canada have pediatric-specific information and indications, respectively. 6 Another Canadian study at a tertiary pediatric hospital showed that 48% of frequently compounded medications were commercially available as childfriendly formulations in the United States or European Union. 7 Both the US and EU have implemented pediatric-targeted policies over the past 2 decades to promote clinical drug research involving children to ensure safe, evidence-based pediatric drug labelling and to encourage the development of pediatric formulations.…”
mentioning
confidence: 99%
“…Ces préparations, réalisées à la pharmacie ou à domicile, ne sont pas en accord avec les normes de fabrication pharmaceutiques et peuvent potentiellement être préjudiciables pour le patient 4 , 5 . Une étude récente a démontré que seulement 47 % et 28 % des monographies de produits de médicaments nouvellement approuvés au Canada comprenaient respectivement des renseignements et des indications, spécifiques à la clientèle pédiatrique 6 . Une autre étude canadienne, réalisée dans un centre hospitalier pédiatrique tertiaire, a révélé que 48 % des médicaments faisant couramment l’objet de préparations magistrales étaient disponibles sur le marché sous forme de préparations adaptées aux enfants aux États-Unis ou au sein de l’Union européenne 7 .…”
unclassified